2020
DOI: 10.6061/clinics/2020/e1759
|View full text |Cite|
|
Sign up to set email alerts
|

Endobronchial ultrasound-guided transbronchial needle aspiration combined with either endoscopic ultrasound-guided fine-needle aspiration or endoscopic ultrasound using the EBUS scope-guided fine-needle aspiration for diagnosing and staging mediastinal diseases: a systematic review and meta-analysis

Abstract: ultrasound-guided transbronchial needle aspiration combined with either endoscopic ultrasound-guided fineneedle aspiration or endoscopic ultrasound using the EBUS scope-guided fine-needle aspiration for diagnosing and staging mediastinal diseases: a systematic review and meta-analysis. Clinics. 2020

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…A previous meta-analysis reported that the sensitivity and specificity of PET-CT for detecting metastatic lymph nodes was 0.78 and 1.00, respectively ( 41 ). Similar results were also reported by previous meta-analyses ( 42 45 ). In the current study, with inclusion of more revelant studies, the sensitivity and specificity was 0.79 and 0.97 for EBUS and 0.74 and 0.99 for EUS, respectively; the staging performance in detecting metastatic lymph nodes was similar to that of PET-CT.…”
Section: Discussionsupporting
confidence: 92%
“…A previous meta-analysis reported that the sensitivity and specificity of PET-CT for detecting metastatic lymph nodes was 0.78 and 1.00, respectively ( 41 ). Similar results were also reported by previous meta-analyses ( 42 45 ). In the current study, with inclusion of more revelant studies, the sensitivity and specificity was 0.79 and 0.97 for EBUS and 0.74 and 0.99 for EUS, respectively; the staging performance in detecting metastatic lymph nodes was similar to that of PET-CT.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the studies show that both the combined EBUS and EUS strategies and the EBUS and EUS-b procedures are valid options for staging. Although some authors have reported higher S values with the first one (87% vs. 84%) [15], and others with the second one (85% vs. 88%) [12], the results are similar for both approaches.…”
Section: Discussionmentioning
confidence: 63%
“…The clinical practice guidelines recommend sampling the mediastinum with minimally invasive techniques, such as endobronchial ultrasound (EBUS) or endoscopic ultrasound (EUS) with fine-needle aspiration, both of which show a diagnostic yield comparable to the mediastinoscopy, which remains the gold standard to date [2,[4][5][6]. Several meta-analyses have shown a higher yield in staging by combining EBUS and EUS as a single technique because it makes it possible to access most lymph node stations and is more sensitive in the detection of lymph node metastasis than EBUS or EUS alone (global sensitivity [S] 0.86-0.91%) [10][11][12][13][14][15]. This increase in S by combining both tests depend on the quality of the procedure [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBUS-TBNA identifies the puncture site through real-time ultrasound guidance, allowing accurate sampling from lesions and cytological and histological diagnosis. The cumulative sensitivity of EUBS-TBNA is 88%-93% and the cumulative specificity is 100% in lymph node staging of lung cancer[ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%